Factors Underlying Defaulting on Antihypertensive Treatment - Alam, Nur; Azhar, MA; Chowdhury, Abdul Wadud; Sabah, KMN; Amin, Md. Rasul (Bangladesh Medical Journal, 2014)
The magnitude of hypertensive patient not continuing treatment is not well documented. But it is assumed that it could be worse and thereby would contribute significantly to mortality and morbidity. A study can produce awareness among all level of medical practitioners regarding the factors underlying defaulting on anti hypertensive treatment. To find out the factors underlying being defaulter of antihypertensive treatment and making future recommendation for remedy - were the main objectives of the present study It was a cross sectional study which was carried out in medical indoor & out patient department of Sir Salimullah Medical College & Mitford Hospital, (SSMC & MH) Dhaka on 100 patients selected by purposive sampling who were defaulters of anti hypertensive treatment. The main causes of becoming defaulters were lack of knowledge and misconception (40%) and financial constrain (32%). The complications of defaulters of antihypertensive treatment were enormous. Most of the patients (80%) suffered from major target organ damage like Stroke/TIA (35%), LVH/LVF/IHD (15%), Retinopathy (12%), Nephropathy (5%) and more than one organ damage (13%). Awareness both of physicians and public about hypertension and proper counseling with education and information about hypertension, rational use of medication and regular follow up will be helpful to avoid morbid complication. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18670 Bangladesh Medical Journal 2011 Vol.40(3):24-27